Strategies for achieving socially equitable and livelihood benefits from culture-based fisheries in Sri Lankan reservoirs - Ekanayake, D.N.B.; Kularatne, M.G.; Petersen, E.H.; Weeratunge, N.; Amarasinghe, U.S.; De Croos, M.D.S.T. (Australian Centre for International Agricultural Research, 2026)
This study examines strategies for achieving socially equitable and livelihood benefits from CBF in Sri Lankan reservoirs. Conducted between October 2023 and March 2024, the research focused on 13 reservoirs across Anuradhapura, Kurunegala and Puttalam districts, selected based on geographical location and reservoir size. A total of 272 fishers, all members of reservoir fisheries societies, participated in face-to-face semi-structured interviews and large group discussions (LGDs). Using a Sustainable Livelihood Framework (SLF)-SWOT analysis, the study identified key socioeconomic, cultural and governance factors influencing equitable livelihood benefits.The research employed both primary and secondary data collection methods, including a pretested household survey complemented by land-use data and annual reports. Data analysis was conducted using IBM SPSS Statistics (Version 22) to generate descriptive statistics and assess relationships between livelihood factors. Findings highlight that social equity and livelihood benefits from CBF vary across reservoir fishing communities, with socioeconomic and governance factors playing a crucial role in shaping outcomes. While opportunities exist to strengthen local governance, enhance capacity building and promote community participation, significant constraints such as policy gaps, financial limitations and inequitable resource distribution hinder progress.To ensure sustainability, effective CBF integration should focus on equity and resilience within fishing communities. Policy enhancements must address governance weaknesses and promote equitable access to CBF benefits while introducing financial support mechanisms for small-scale fishers. Capacity building should be prioritised by empowering fisheries societies in decision-making and providing training for sustainable fishing practices. Community engagement and collaboration through participatory governance models and partnerships with local authorities, research institutions and fishing communities can further drive progress. For future research, long-term studies on the impact of CBF on social equity and livelihoods are essential, alongside an exploration of gender dynamics to develop more inclusive fisheries policies. These measures can contribute to a more equitable and sustainable reservoir fishery system.
Keywords: Culture-based fisheries; Socially equitable; Livelihoods